IMPROVING HIGH SCHOOL STUDENTS SPEAKING ABILITY BY USING THE CARTOON PICTURES SERIES - Ndoen, Jessica Sarsiana (English Language Education Study Program, 2023)
This study is aimed to identify whether cartoon images can assist high school students at SMP N 5 Kota Kupang in improving their speaking abilities. The descriptive method was used to characterize speaking performance of the students. This particular study employs a speaking assignment as the research instrument to collect data and focuses on three distinct elements of speaking: grammar, vocabulary, and pronunciation. According to the findings, it was discovered that (1) eighth-grade students could speak English, particularly when describing cartoon picture series orally. (2). students in the eighth grade showed a 'very good' speaking ability level (15.6). (3). the students speaking ability level for each element: Grammar; (M=5.20), vocabulary (M=5.40), and pronunciation (M=5.00). There are some recommendations based on the results of the research. It is recommended for the English teachers to train students to speak English effectively by using interesting media, such as pictures or videos, and encourage them to read more to improve their literacy skills. Secondly, the students need to work on their pronunciation by listening to English-language podcasts, music, and television shows. Future researchers are encouraged to conduct similar research with broader media and strategies to improve language learners' speaking ability